2020
DOI: 10.17263/jlls.712849
|View full text |Cite
|
Sign up to set email alerts
|

Development of a training module to improve initial ELT proficiency among student-teachers in multi-ethnic community schools

Abstract: APA Citation:Xiao, Y., Surasin, J., & Prabjandee, D. (2020). Development of a training module to improve initial ELT proficiency among student-teachers in multi-ethnic community schools. AbstractThis study aimed to investigate the current needs of student-teachers' professional development, develop a training module to improve their initial ELT proficiency and determine its effectiveness. The mixed methods research design with parallel strategy, starting with the quantitative and following by the qualitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…This implies that thorough training is required for professionals in the field to overcome such obstacles. This is congruent to previous study [19] investigating the needs of studentteachers professional development. It was found that training on a module is one of the challenges that they experienced.…”
Section: "To Be Honest I'm Having Difficulty Determining Where To Beg...supporting
confidence: 92%
“…This implies that thorough training is required for professionals in the field to overcome such obstacles. This is congruent to previous study [19] investigating the needs of studentteachers professional development. It was found that training on a module is one of the challenges that they experienced.…”
Section: "To Be Honest I'm Having Difficulty Determining Where To Beg...supporting
confidence: 92%
“…So, the learning activity become effective. It is also important to know, either the teaching strategies applied by the teacher were in accordance with the I2M3 standard process or not (Darmawati et al, 2020;Saleh, 2021;Xiao et al, 2020). Firstly, for the interactive teaching strategies teacher apply reviewing strategies, which in the beginning of the class, the teacher asked the students about what they have learned in the previous meeting.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the implemented method was still conventional and straightforward and could not motivate the trainees to maximize the training process. The training process must be supported by exciting methods and suitable training materials that are adequate and relevant to the progress of the current era (Oksa & Soenarto, 2020;Xiao et al, 2020;Logan et al, 2020). The conducted training conditions only had materials in the form of PowerPoint slides displayed on a projector consisting of short and more straightforward sentences causing lower understanding and mastery of the participants.…”
Section: Discussionmentioning
confidence: 99%